ANALISIS FRAMING PEMBERITAAN KASUS KEMATIAN JURNALIS METRO TV YODI PRABOWO PADA MEDIA ONLINE TEMPO.CO - Indrawan Indrawan; Muh. Nur Latief; Suryani Musi (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2021)
The study aims to find out how Tempo.co frame news of Yodi Prabowo's death by using Robert Entman's Framing analysis model. A total of 84 news stories were collected, eight news samples were taken for analysis. Based on the results of the analysis of framing model Robert Entman the author concluded that Tempo.co tend to raise the case of the death of the Metro TV editor as a matter of romance, namely Tempo.co tend to tell about the police information about the testimony of the victim's lover and also a third person in their relationship. Tempo.co also highlighted the facts of the investigation, witness examination, autopsy results, and other evidence that narrowed to the conclusion of Yodi Prabowo's death (Define Problem). Tempo.co seeks to display something as is happening on the ground and highlight facts about police information such as autopsy results and the involvement of others in the case of Yodi Prabowo's death.